Peripheral Vascular Disease: A Contemporary Review - Muhammad Bashar, Abul Hasan; Ahmed, Mohsin (Bangladesh Heart Journal, 2019)
Peripheral Vascular Disease (PVD) is an emerging public health problem in Bangladesh that has tremendous social and economic implications. Unfortunately, there is a general lack of adequate understanding about this disease among primary care physicians and common people. This is why patients present late to vascular care which poses significant difficulties in the treatment and increases cost burden. Late presentation also increases the rate of limb loss. Treatment of PVD is rapidly evolving with the advent of endovascular modalities. The article provides a review of the basic aspects of PVD as well as the present status of care. Bangladesh Heart Journal 2019; 34(2) : 137-145